2019
DOI: 10.3390/ijerph16204018
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequality Among the Elderly in Rural China and Influencing Factors: Evidence from the Chinese Longitudinal Healthy Longevity Survey

Abstract: Based on data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), this paper calculates the health distribution of the elderly using the Quality of Well-Being Scale (QWB) score, and then estimates health inequality among the elderly in rural China using the Wagstaff index (WI) and Erreygers index (EI). Following this, it compares health inequalities among the elderly in different age groups, and finally, uses the Shapley and recentered influence function-index-ordinary least squares (RIF-I-OLS) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(29 reference statements)
0
14
0
1
Order By: Relevance
“…More than half of the studies ( n = 12) reported income‐ or wealth‐related discrimination 6,8,13,14,16–18,21,22,24–26 . The majority of the studies were conducted in China except one in South Korea, 14 one in the USA, 18 and one in Italy, Spain, and Portugal 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the studies ( n = 12) reported income‐ or wealth‐related discrimination 6,8,13,14,16–18,21,22,24–26 . The majority of the studies were conducted in China except one in South Korea, 14 one in the USA, 18 and one in Italy, Spain, and Portugal 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Access to primary care also demonstrated a pro‐rich inequality 8 . Seven studies from China highlighted pro‐poor inequality in accessing elder care in health facilities 6,16,17,21,22,25,26 . Another study from China revealed a difference in health service utilization among the floating elderly population irrespective of insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
“…The standard CI requires that the outcome variable is on the same scale of income, that is, measured on a ratio scale [ 21 ]; if the outcome variable is binary, the standard CI needs to be revised. This study adopted the Erreygers’ modified index ( E I ) given by [ 19 , 21 , 22 ]: where h max and h min are the upper and lower bounds of outcome variables, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers found that inequalities in health favor the rich [6][7][8]. In particular, the rich are less likely to have limitations on their physical abilities and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Region is another significant socioeconomic factor related to health inequality. Living in Central or Western China has a close relationship with higher functional disability, compared to those living in Eastern China [8]. People living in rural areas are more likely to experience functional limitations in daily activities [11].…”
Section: Introductionmentioning
confidence: 99%